Towards Sustainable Residential Buildings in Hot Arid Climates: Learning from Traditional Architecture of the Souf Region (Algeria) - Femmam, Asma; Sriti, Leila; Latreche, Sihem (Technium Social Sciences Journal, 2022)
In southern Algeria, the local traditional settlements have been generated as a response to material, spiritual and cultural needs of people, whilst, they have also succeeded to respond to one of the harshest climates on the planet. In this respect, the vernacular dwelling of the Souf region provides a very instructive example of what is now called sustainable architecture. Furthermore, the traditional architecture of the Souf embodies ingenious cooling design strategies relevant to occupant behaviour, environment adaptation, techniques and local materials that can offer great opportunities to overcome the desert climate conditions regarding the contemporary buildings. The present research addresses the issue by performing a qualitative analysis on two case studies that were selected to represent respectively typical traditional dwellings and common contemporary residential buildings. Based on in-field collected data, the selected examples were analysed in order to assess and compare their thermal performance and climatic adaptability. The sustainable passive design features used in the traditional dwelling were specified, evaluated and then the potential to use them as design alternatives at the early architectural design stage of contemporary housing projects was explored. Finally, a set of recommendations that illustrates the convenient passives strategies is provided for application in hot arid climates.